Quantification of the Landscape for Revealing the Underlying Mechanism of Intestinal-Type Gastric Cancer - Yu, Chong; Wang, Jin (Frontiers in Oncology, 2022)
Gastric cancer is a daunting disease with a fetal impact on global health. Gastric cancer has become the fourth most common cancer and the second most frequent cause of cancer death nowadays. According to the Lauren classification, gastric cancer can be divided into two types: intestinal and diffuse types. The intestinal-type gastric cancer is more common in elder people and atrophic gastritis (AG) and intestinal metaplasia (IM) are proved to be the main precursor lesions of the intestinal-type gastric cancer (IGC). Furthermore, Helicobacter pylori infection has been considered as the most significant cause of AG and IM. In this study, we aim to find out the mechanism of IGC progression and figure out how the Helicobacter pylori infection induces the IGC. We collected the key genes of gastric cancer and the specific genes of IGC through literature research. Then we use these genes to build up a gene regulatory network of IGC. Based on the gene regulatory network, we quantified the landscape of IGC. On the landscape, there are three stable states which can be identified as normal, AG and the gastric cancer state. Through the landscape topography, we can figure out the biological features and cancer progression of IGC . To investigate the influence of Helicobacter pylori infection on IGC, we simulated different degrees of Helicobacter pylori infection. When the infection of Helicobacter pylori become more and more serious, the landscape topography changed accordingly. IM state is emerged on the landscape. Through the landscape topography variations, we can find out the influences of Helicobacter pylori infection of IGC. At last, we use global sensitivity analysis to search the key regulations which are more sensitive on IGC prevention or therapy strategy. This study presents a new approach and novel model to explore the mechanism of IGC. The simulations of different degrees of Helicobacter pylori infection can provide us a system view of IGC progression. The key regulations can give us some insights and guidance on clinical trails or experimental studies.